Expressed Sequence Tags from Phytophthora sojae Reveal Genes Specific to Development and Infection - Trudy A. Torto-Alalibo; Sucheta Tripathy; Brian M. Smith; Felipe D. Arredondo; Lecong Zhou; Hua Li; Marcus C. Chibucos; Dinah Qutob; Mark Gijzen; Chunhong Mao; Bruno W. S. Sobral; Mark E. Waugh; et al. (Molecular Plant-Microbe Interactions, 2007)
Six unique expressed sequence tag (EST) libraries were generated from four developmental stages of Phytophthora sojae P6497. RNA was extracted from mycelia, swimming zoospores, germinating cysts, and soybean (Glycine max (L.) Merr.) cv. Harosoy tissues heavily infected with P. sojae. Three libraries were created from mycelia growing on defined medium, complex medium, and nutrient-limited medium. The 26,943 high-quality sequences obtained clustered into 7,863 unigenes composed of 2,845 contigs and 5,018 singletons. The total number of P. sojae unigenes matching sequences in the genome assembly was 7,412 (94%). Of these unigenes, 7,088 (90%) matched gene models predicted from the P. sojae sequence assembly, but only 2,047 (26%) matched P. ramorum gene models. Analysis of EST frequency from different growth conditions and morphological stages revealed genes that were specific to or highly represented in particular growth conditions and life stages. Additionally, our results indicate that, during infection, the pathogen derives most of its carbon and energy via glycolysis of sugars in the plant. Sequences identified with putative roles in pathogenesis included avirulence homologs possessing the RxLR motif, elicitins, and hydrolytic enzymes. This large collection of P. sojae ESTs will serve as a valuable public genomic resource.